Educação ambiental: a prática do pedagogo em escolas da rede municipal de ensino de Curitiba - Kusma, Elis Natalina (2017)
This study has the objective of researching Environmental Education in the practice of the pedagogue and as a subject the pedagogues that work in the Schools of the Municipal Network of Education of Curitiba, the research question being: How is the practice of the pedagogue in the focus of Environmental Education in Elementary schools of the Regional Nucleus of Education of the Industrial City of Curitiba (NRECIC) of the Municipal Network of Education of Curitiba? The objectives are: to analyze the Environmental Education in the practice of the pedagogues that work in the basic education schools of the Municipal Education Network of Curitiba; Characterizing and analyzing the pedagogical practice in the approach of the actions of Environmental Education in the schools researched before the policy of Environmental Education in force. The methodology is based on the qualitative research approach. The data collection used documents, observation and interviews with ten pedagogues, in seven schools of the Municipal Education Network of Curitiba, located in the Industrial City of Curitiba and in the area covered by the Barigui river basin. In this research the analysis of the Political Educational Projects and analysis of the content of the interviews with the pedagogues of said schools were considered. The results point out: to the outstanding confirmation of the pedagogues' performance accumulating the pedagogical and administrative activities in the management of the researched schools; The pedagogues are not aware of the current legislation and the projects and programs of Environmental Education existing in the Municipal Network of Education; Superficial understanding about Environmental Education when considering that the practice of Environmental Education is linked to the area of Sciences; Understand Environmental Education in the focus of conservative and pragmatic tendencies; Recognize that the theme of Environmental Education should be worked on in the school; As regards physical spaces partially attend to the aspects of sustainability and development of socioenvironmental practices; Unanimously report the lack of training related to Environmental Education. In addition, it was verified that Environmental Education expanded its space in educational policies, being specifically treated as one of the principles in the Curricular Guidelines of the Curitiba Municipal School Network (2006) in force and in the current Curricular Plan (2016). It was found that Environmental Education is present in a small number of Pedagogical Political Projects of the schools surveyed. It was verified as challenges to work with Environmental Education in the schools studied the necessary continuing education of the pedagogues in the perspective of Environmental Education, in view of its attribution in the pedagogical management of the school and the adequate infrastructure to materialize the school practices of Education Environmental.